2020
DOI: 10.1101/2020.09.24.20201236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioural barriers to COVID-19 testing in Australia

Abstract: Background: The current suppression strategy for COVID-19 in Australia is dependent on people getting tested and self-isolating while they have COVID-19 symptoms. However, there is very little research on the behaviours and behavioural barriers involved in getting tested, both in Australia and worldwide, despite there being some evidence that these barriers do exist. Methods: The Sydney Health Literacy Lab (SHeLL) has been conducting a national longitudinal survey in Australia since April 2020. A list of testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Lateral flow testing is less widely represented in the evidence base and is more likely to feature in articles and preprints based on more recently collected data [ 22 , 38 ]. The characteristics of all studies included in the review are summarized in Table 1 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lateral flow testing is less widely represented in the evidence base and is more likely to feature in articles and preprints based on more recently collected data [ 22 , 38 ]. The characteristics of all studies included in the review are summarized in Table 1 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 …”
Section: Resultsmentioning
confidence: 99%
“…Studies that explored facilitating factors included research on participants’ knowledge and awareness of testing types and how they work [ 36 , 44 ] and research on people’s identification and interpretation of COVID-19 symptoms, including how this affects test-seeking behavior [ 30 , 45 , 46 , 47 ]. Multiple studies in this research area gathered data on people’s self-reported motivations for undergoing or avoiding testing [ 22 , 23 , 24 , 26 , 27 , 29 , 30 , 32 , 35 , 37 , 38 , 40 , 41 , 42 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Some of these studies sought to gather data on people’s trust in the government and/or medical systems in relation to COVID-19 testing [ 24 , 41 , 54 , 55 ] or piloted ways to improve people’s levels of trust in testing [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little published research exploring why some parents may not present children for COVID‐19 testing. A recent Australian study has identified barriers to testing among adults, including a belief that testing is painful, a lack of knowledge about how to get tested, and worry about getting infected at the testing centre 3 . These barriers may also apply to parents in relation to testing for children.…”
mentioning
confidence: 99%